Analysis of Business Development Strategy for Floriculture Processing Products at CV Telogo Budhoyo Malang - Yohana Farmita Go; Cakti Indra Gunawan; Umi Rofiatin (International Research & Development for Human Beings (IRDH), 2026)
The flower board business is a type of business that has the potential to grow along with the increasing public demand for greeting media at various events such as weddings, condolences, and inaugurations. This study aims to analyze internal and external factors that influence business development and formulate an appropriate development strategy at CV Telogo Budhoyo Malang. The research method used is a descriptive method with a SWOT analysis approach. The data used in this study consists of primary and secondary data obtained through interviews, observations, and distribution of questionnaires to business owners, employees, and customers. The results of the study indicate that internal factors that are strengths include good product quality, the use of fresh flowers, and a diverse product variety. Meanwhile, weaknesses include limited human resources and production equipment. External factors indicate opportunities in the form of increasing market demand and the development of digital marketing media, while threats come from competition from similar businesses and fluctuations in raw material prices. Based on the SWOT analysis, several alternative business development strategies were obtained, including increasing product innovation, expanding marketing through digital media, improving service quality, and strengthening business management. These strategies are expected to increase the competitiveness and sustainability of CV Telogo Budhoyo Malang.